Indirect cytocompatibility of a low-concentrated hydrogen peroxide bleaching gel to odontoblast-like cells - Soares, Diana Gabriela de Souza [UNESP]; Marcomini, Natália [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Pansani, Taisa Nogueira [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (Wiley, 2015)
Aim To assess the initial cytotoxicity and the late phenotype marker expression of odontoblast-like cells (MDPC-23) subjected to less aggressive in-office bleaching therapies. Methodology A 17.5% hydrogen peroxide (H2O2) gel was applied for 45, 15 or 5 min to enamel/dentine discs adapted to trans-wells positioned over cultured MDPC-23 cells. No treatment was performed on the negative control. Immediately after bleaching, the cell viability, gene expression of inflammatory mediators and quantification of H2O2 diffusion were evaluated. The ALP activity, DSPP and DMP-1 gene expression and mineralized nodule deposition (MND) were assessed at 7, 14 or 21 days post-bleaching and analysed statistically with Mann–Whitney U-tests (α = 5%). Results H2O2 diffusion, proportional to treatment time, was observed in all bleached groups. Reductions of approximately 31%, 21% and 13% in cell viability were observed for the 45-, 15- and 5-min groups, respectively. This reduction was significant (P < 0.05) for the 45- and 15-min groups, which also presented significant (P < 0.05) over-expression of inflammatory mediators. The 45-min group was associated with significant (P < 0.05) reductions in DMP-1/DSPP expression at all periods, relative to control. The ALP activity and MND were reduced only in initial periods. The 15-min group had less intense reduction of all markers, with no difference to control at 21 days. Conclusions The 17.5% H2O2 applied to tooth specimens for 5 min caused no alteration in the odontoblast-like cells. When this gel was applied for 45 or 15 min, a slight cytotoxicity, associated with alterations in phenotypic markers, was observed. However, cells were able to recover their functions up to 21 days post-bleaching.
Keywords: Cell differentiation; Cytotoxicity; Odontoblasts; Tooth bleaching